Study of terrain correction computation using square pattern and sloped triangle methods in Karangsambung. Issue 1 (1st May 2022) - Salam, R A; Wahyudi, E J; Setianingsih,
Abstract: Conventional assessments of terrain correction are carried out by laying transparent paper containing the Hammer chart on topographic maps, then estimating the elevation for each of Hammer chart's compartment. This procedure has disadvantages, the number of compartments is too small, and there is a subjectivity from the observer in estimating the compartment's height, especially in an area with varied topography, such as Karangsambung. These research aims are to study the effect of the topography around Karangsambung on terrain correction value and to overcome problems in conventional terrain correction estimation. Estimation of terrain correction carried out using square pattern and sloped triangle method, where the area around measurement points divided into square and triangle compartment. Based on the results, South Seraju Ranges, with an altitude of 1000 m at a distance of 20 – 30 km from Karangsambung gives an effect of 0.05 mGal on terrain correction, while the Quaternary Volcano with height of 3000 m at range of 30 – 40 km gives the effect of 0.1 mGal. The results of applying the program at the gravity data show that the use of the square pattern and sloped triangle method can correct errors from conventional estimation up to 3 mGal.